THU0326 Relationship between Regular Exercise, Functional Capacity and Quality of Life in Pacients with Fibromyalgia. (10th June 2014) - Alina, S.
Abstract : Background: Fibromyalgia (FM) is a chronic musculoskeletal disorder characterized by generalized muscular pain accompanied by fatigue and tenderness at specific anatomical sites called tender points; additionally other associated symptoms include altered sleep, with cognitive and emotional disturbances as anxiety and depression, leading to disability and poor quality of life. Various exercise programs are accepted as treatment for FM, with complex actions on different muscular groups, leading to pain decrease, postural equilibrium and mobility improvement. Objectives: Verify the relationship between functional capacity as well as a self report of quality of life with the practice of regular exercise in patients with FM Methods: A total of 320 patients diagnosed with FM were recruited between May of 2012 and December of 2013 from Rehabilitation outpacients clinics in Romania. The patients were divided in two groups. Group1 included patients who reported practice of regular exercise (n=170; 50, 7±13, 04 years), while group 2 included those who reported non-practice of regular exercise (n=150; 49±20 years). Functional capacity and quality of life was measured using the Health Assessment Questionnaire-HAQ and Short Form – SF-36 Results: Significant differences in the quality of life and functional capacity were observed when group 1 was compared with group 2. A lower score of functional capacity (HAQ) was found in group 2when compared with the group 1 (p=0, 0006). Higher values were obtained for the group 1 when compared with group 2 for the following domains of SF-36: physical functioning (p<0, 001) and bodily pain (p<0.05). No significant differences were found for role physical, general health, vitality, social functioning, role emotion and mental health domains. Conclusions: Regular exercise showed a positive impact in the functional capacity and quality of life in patients with FM. References: Ann Rheum Dis 2011;70(Suppl 3):765 Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1615